2018
DOI: 10.1038/nature25462
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM shows how dynactin recruits two dyneins for faster movement

Abstract: Dynein and its cofactor dynactin form a highly processive microtubule motor in the presence of an activating adaptor, such as BICD2. Different adaptors link dynein/dynactin to distinct cargos. Here we use electron microscopy (EM) and single molecule studies to show that adaptors can recruit a second dynein to dynactin. Whereas BICD2 is biased toward recruiting a single dynein, the adaptors BICDR1 and HOOK3 predominantly recruit two. We find that the shift toward a double dynein complex increases both force and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
399
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(440 citation statements)
references
References 56 publications
20
399
0
Order By: Relevance
“…In one conformation, the alpha helix extends out from the body of the mushroom; in the other, it is oriented closer toward the surface of the α-subunit’s globule domain (PDB 3AAE, 11ZN,2KZ7, 2KXP) (Takeda et al, 2010; Yamashita et al, 2003; Zwolak et al, 2010a). Structures of CP bound to the actin-like Arp1 filament in dynactin complex, derived from cryoEM, also show the β-tentacle in an α-helical conformation, in contact with actin (Urnavicius et al, 2015; Urnavicius et al, 2018), and in a position consistent with the model for CP binding to actin (Narita et al, 2006). …”
Section: Resultsmentioning
confidence: 55%
“…In one conformation, the alpha helix extends out from the body of the mushroom; in the other, it is oriented closer toward the surface of the α-subunit’s globule domain (PDB 3AAE, 11ZN,2KZ7, 2KXP) (Takeda et al, 2010; Yamashita et al, 2003; Zwolak et al, 2010a). Structures of CP bound to the actin-like Arp1 filament in dynactin complex, derived from cryoEM, also show the β-tentacle in an α-helical conformation, in contact with actin (Urnavicius et al, 2015; Urnavicius et al, 2018), and in a position consistent with the model for CP binding to actin (Narita et al, 2006). …”
Section: Resultsmentioning
confidence: 55%
“…Structural analysis revealed that most of these mutations (7 out of the 8) clustered to two distinct regions: (1) adjacent to, or within the N-terminal dimerization domain, or (2) at a surface that interfaces with the intermediate chain of a neighboring heavy chain in a 2 dynein:1 dynactin complex ( Figure 2, Supplement 4). This latter region was recently identified as being important to stabilize the binding of a second dynein complex to dynactin, and ensuring that all four heavy chains are properly aligned for efficient motility of the human dynein-dynactin complex 74 . Our data suggest that the ability to recruit 2 dynein complexes to dynactin is conserved in yeast, and that disrupting this complex can compromise force generation ( Fig.…”
Section: Spindle Tracking In Live Cells Provides a Sensitive Read Outmentioning
confidence: 99%
“…The first and obvious possible player is dynactin, known to be essential to cortical pulling forces and able to make dynein more processive (Skop, 1998;Gonczy et al, 1999;King and Schroer, 2000;Rodriguez-Garcia et al, 2018). Beyond, some other players were involved in other systems in vitro or in vivo, for example: the end-binding (EB) proteins putatively involved in initiating dynein pulling once a microtubule is captured (Jha et al, 2017), and whose homolog EBP-2 contributes, although modestly, to cortical forces (Rodriguez-Garcia et al, 2018); LIS-1 essential for spindle positioning in nematode and reported to be also implicated in dynein regulation beyond its classic inhibitory role (Cockell et al, 2004;Baumbach et al, 2017;DeSantis et al, 2017); BICD-1 BICD2 involved in nuclear migration in nematode hypodermis (Fridolfsson et al, 2010) but no strong early embryonic phenotype was reported, despite indication of its role in other organisms (Swan et al, 1999;Splinter et al, 2012;Jha et al, 2017;Urnavicius et al, 2018). Thirdly and finally, efficient pushing by microtubules against the cortex requires some microtubuleassociated proteins to prevent the switch to catastrophe (Janson et al, 2003).…”
Section: Which Molecular Mechanisms Could Regulate These Forces?mentioning
confidence: 99%